2021
DOI: 10.1021/acsanm.1c00803
|View full text |Cite
|
Sign up to set email alerts
|

Improving Gas Selectivity in Membranes Using Polymer-Grafted Silica Nanoparticles

Abstract: Herein, we demonstrate that tuning of structural parameters and material chemistry enables control of the permeability and selectivity of gases (CO 2 , He, and CH 4 ) in membranes based on poly(butyl methacrylate)-grafted nanoparticles (PGNs). Our data show that the presence of nanoparticles and the overall dense packing of grafted chains noticeable in PGNs with low grafting density have an adverse effect on the diffusivity of gases. This effect is compensated by an improvement in the solubility of CO 2 gas pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…We have attempted to use extended Maxwell models as suggested in the literature, separately above and below the maximum permeability: we assume that the dry region has significantly higher permeability than the interpenetrated zone, while the NP core is not permeable. This model does not capture the trends observed in Figure , in agreement with previous conclusions of Bocherova and co-workers …”
Section: Results and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We have attempted to use extended Maxwell models as suggested in the literature, separately above and below the maximum permeability: we assume that the dry region has significantly higher permeability than the interpenetrated zone, while the NP core is not permeable. This model does not capture the trends observed in Figure , in agreement with previous conclusions of Bocherova and co-workers …”
Section: Results and Discussionsupporting
confidence: 82%
“…This model does not capture the trends observed in Figure 4, in agreement with previous conclusions of Bocherova and coworkers. 42 We thus resorted to a more empirical approach. For ϕ NP > ϕ NP,max , we used a variety of forms, including an exponential, a hyperbolic tangent, and a power law to see which one adequately describes the data.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“… 141 Experiments by Jeong et al using poly(butyl methacrylate)-grafted particles show that high grafting densities are required for increased gas permeability. 144 This is attributed to the formation of polymer bridges between particles at low grafting densities, either during polymerization or by penetration of polymer chains from one particle to the surface of another, which can result in inhomogeneous dispersion of the particles. Xin et al found that brush functionalization with polystyrene-derived polymers improved the compatibility of various inclusions with a sulfonated poly(ether ether ketone) (SPEEK) matrix.…”
Section: Applicationsmentioning
confidence: 99%
“…Pure GNP melts display significant improvements in their gas transport properties relative to the corresponding neat polymer, making them germane to direct air capture and natural gas separations. ,, For a fixed grafting density (we mostly employ σ ≈ 0.47 chains/nm 2 but have systematically examined σ ≈ 0.11–0.66 chains/nm 2 ), we demonstrated a nonmonotonic gas permeability enhancement as a function of graft chain molecular weight (MW g ), with a peak in the vicinity of MW g ≈ 100 kDa for σ ≈ 0.47 chains/nm 2 (see Supporting Information, Figure S1). ,, Moreover, gas penetrants with larger kinetic diameters appear to have increased enhancements . We seek to understand this unusual behavior, especially the gas transport maximumspecifically, here we explore whether the packing structure of the GNP layer (and hence of the NPs) could indirectly influence the diffusivity of light gases through GNP membranes.…”
Section: Introductionmentioning
confidence: 97%